2010
DOI: 10.4103/0972-3919.72692
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse hepatic and splenic Tc-99m MDP tracer uptake in case of multiple myeloma

Abstract: Tc-99m methylene diphosphonate (MDP) bone scintigraphy has long been used for the evaluation of benign as well as malignant skeletal conditions. However, non-osseous tracer uptake on a bone scan is an unusual finding. There is a need to understand the pathophysiological basis of the non-osseous uptake, which may have a clinical relevance or deteriorating effect on the quality of the bone scan. We describe a case of multiple myeloma, where extraosseous uptake in the form of diffuse hepatic and splenic uptake, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Diffuse and intense hepatic uptake of bone imaging agent can also be due to a variety of causes including, diffuse hepatic necrosis, repeated iron injections, administration of contrast media after bone scan agent injection, idiopathic hepatic uptake, acute hypoxic hepatitis or hypoxia secondary to respiratory failure, amyloidosis associated with plasma cell dyscrasia and also in late stage of multiple myeloma. [ 10 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse and intense hepatic uptake of bone imaging agent can also be due to a variety of causes including, diffuse hepatic necrosis, repeated iron injections, administration of contrast media after bone scan agent injection, idiopathic hepatic uptake, acute hypoxic hepatitis or hypoxia secondary to respiratory failure, amyloidosis associated with plasma cell dyscrasia and also in late stage of multiple myeloma. [ 10 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, nonosseous uptake of bone-seeking radiopharmaceuticals is observed in different conditions and organs which are necessary to distinguish the pathophysiological causes [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] In another study, Sood et al reported that Tc-99m-hydroxy-methane-diphosphonate bone scan results in diffuse and high hepatic uptake, hypoxia from respiratory failure, and the development of hepatic necrosis in MM patients. [ 12 ] Adenosine monophosphate-activated protein kinase activator metformin has been demonstrated to have synergistic effects with dexamethasone against MM and to decrease myeloma proliferation through the IGF-1R/PI3K/AKT/mTOR pathway. [ 13 ] Although there are no direct studies linking methane-containing compounds to MM, there may be an association in the context of ligand and cell adhesion-mediated drug resistance.…”
Section: Introductionmentioning
confidence: 99%